2009
DOI: 10.1186/1746-4269-5-14
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedical survey of Berta ethnic group Assosa Zone, Benishangul-Gumuz regional state, mid-west Ethiopia

Abstract: Traditional medicine (TM) has been a major source of health care in Ethiopia as in most developing countries around the world. This survey examined the extent and factors determining the use of TM and medicinal plants by Berta community. One thousand and two hundred households (HHs) and fourteen traditional healers were interviewed using semi-structured questionnaires and six focused group discussions (FGDs) were conducted. The prevalence of the use of TM in the two weeks recall period was 4.6%. The HH economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 15 publications
16
92
0
Order By: Relevance
“…Like the present study, the local community elsewhere in Ethiopia collects medicinal plants both from the wild and semi-wild environments 13 24 and Mesfin et al 27 in the humid areas, and Adefa 1 , Zenebe et al 35 , Yirga 33,34 in semi-arid areas of Ethiopia also documented an appreciable number of medicinal plants.…”
Section: Floristic Composition Diversity and Distribution Of Medicinsupporting
confidence: 50%
See 1 more Smart Citation
“…Like the present study, the local community elsewhere in Ethiopia collects medicinal plants both from the wild and semi-wild environments 13 24 and Mesfin et al 27 in the humid areas, and Adefa 1 , Zenebe et al 35 , Yirga 33,34 in semi-arid areas of Ethiopia also documented an appreciable number of medicinal plants.…”
Section: Floristic Composition Diversity and Distribution Of Medicinsupporting
confidence: 50%
“…Flatie et al 13 and Lulekal et al 24 also found roots take the highest proportion due to the efficacy of roots in treating the ailments. Conversely, leaves were the most widely used parts of plants 1,2,28,32,35 .…”
Section: Utilization and Socioeconomic Implicationmentioning
confidence: 97%
“…The most frequently used plant parts are bark (79%), leaves (11%), roots (7.5%) and stalks (2.1%) ( Figure 1A). It is well recognized by conservationists that medicinal plants primarily valued for their root parts and those which are intensively harvested for their bark often tend to be the most threatened by over-exploitation (Flatie et al, 2009). This is the case with all Warburgia species, with its users targeting mainly stem bark as source of ethnomedicine.…”
Section: Vernacular Names and Traditional Usesmentioning
confidence: 99%
“…(Sterculiaceae), is used in Burkina Faso folk medecine. Leaves, bark, roots or the whole plant are used against swelling, toothache, colic, rheumatism, ear infections, asthma, cough, diarrhea, dysentery, conjunctivitis, wounds, abscess (Flatie et al, 2009;Adjanohoun et al, 1989;Ruffo, 1991;Zerbo et al, 2007, Zongo, 2013. Miyashiro et al (1994) showed that aqueous and methanolic extracts of Waltheria indica L. had a significant inhibition of HIV-1 protease.…”
Section: Introductionmentioning
confidence: 99%